Fishbase a biological database on fish-concepts, designs and data sources. - Froese, R. and Pauly, D. (Manila, Philippines ICLARM, 1994)
ICLARM Conference Proc. 64
Keywords: Data collections; FishBase (Computer file); Fishery biology; Fishery resources